Enjeux transfrontaliers en période de pandémie de la Covid-19 : le cas de la circulation sur l’Oyapock entre Guyane française et Brésil - Stéphane Granger; Gutemberg de Vilhena Silva (Confins)
In the middle of the Amazon, the Oyapock River separates the French Collectivity of Guiana and the Brazilian state of Amapá. Link between two shores separated by distinct sovereignties but subject to a common isolation within their respective groups, the Oyapock, a river waterway essential to local traffic, saw its role as a political and economic barrier throughout the 20th century. reinforced by the will to reappropriate States. At the same time, institutional cooperation agreements formalized its role as an interface while seeking to limit migratory flows. Decisions taken at the national level attempt to impose a filtering barrier function that the health crisis of 2020-2021 brought, even temporarily, to its peak to the detriment of local solidarity.